2020
DOI: 10.3390/ijerph18010175
|View full text |Cite
|
Sign up to set email alerts
|

Availability of Essential Medicines in a Country in Conflict: A Quantitative Insight from Yemen

Abstract: Background: Medicine and medical supplies are often in short supply in countries suffering from the scourge of conflict. Effective medicine supply policies are lacking in many low- and middle-income countries (LMICs), particularly during conflict. This study aimed to assess the availability of essential medicines in both the public and private healthcare sectors. Methods: The study was conducted by administering a survey from November 2017 to February 2018 using the World Health Organization/Health Action Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…In the current study, key informants mentioned that the facilities encountered supply chain disruptions from the scourge of conflict in the western part of the country. Similarly, conflict and political instability affected the supply of essential medicines in the Middle East, like in Yemen [ 60 ]. This is linked to the poor engagement of government for the basic human needs and diversion of financial and human resources for immediate conflict-related actions and responses.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, key informants mentioned that the facilities encountered supply chain disruptions from the scourge of conflict in the western part of the country. Similarly, conflict and political instability affected the supply of essential medicines in the Middle East, like in Yemen [ 60 ]. This is linked to the poor engagement of government for the basic human needs and diversion of financial and human resources for immediate conflict-related actions and responses.…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent study by Chow et al published in 2020, the availability of all three types of cardiovascular medicines (blood pressure lowering medicines, anti-platelets and statins) was 50%, 62.8% and 87.2% respectively [ 14 ]. Another recent study in the Middle East shows cardiovascular medicine availability of 36.6–52.5% [ 15 ]. In East Africa, average availability of cardiovascular medicines in one study was 55.7%, while in another study antihypertensive medicine availability was 0–28.5% and heart failure medication availability was 0.5–49.5% [ 16 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…In 2022, a large study reported 19.03–76.9% availability for LPG in the public sector and 41.1–80.49% availability of LPG in the private sector [ 18 ]. Availability of cardiovascular medicines is lower in public health facilities than private facilities in LMICs [ 9 , 13 , 15 , 18 ]. Branded medicines are less available than generic medicines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…42,64,101,102,112 Of the 88 studies included in the review, only ve studies described the provision of family planning and contraception services, 40,48,52,70,103 screening for HIV/AIDS and management of acute sexually transmitted infections were carried out in four studies, 50,56,58,81 health promotion activities for lifestyle changes in chronic diseases and good hygiene practices were identi ed in ve studies, 56,62,86,92,101 and interventions for smoking cessation were identi ed in one study. 43 Monitoring of patients with hypertension was outlined in seven studies 35,38,71,74,78,87,98 ; only one study described screening for both type 2 diabetes mellitus and hypertension, while promotion of access to essential medicines was observed in ve studies, 47,64,77,79,85,117 antiepileptic medicines for children, 41 anticancer medicines, 80,99 medicines for cardiovascular diseases, 55 antibiotics and medicines for childhood diarrhoeal illness, 32,73,82,83,105,113 and medicines for migraine headaches. 94 Another study reported screening for osteoporosis in a population of high-risk women.…”
Section: Search Strategymentioning
confidence: 99%